Designing artificial circadian environments with multisensory cares for supporting preterm infants’ growth in NICUs - Arimitsu, Takeshi; Fukutomi, Rika; Kumagai, Mayuko; Shibuma, Hayato; Yamanishi, Yoko; Takahashi, Kei-ichi; Gima, Hirotaka; Seto, Yoshitaka; Adachi, Hiroyuki; Arai, Hirokazu; Higuchi, Masakatsu; Ohgi, Shohei; et al. (Frontiers in Neuroscience, 2023)
Previous studies suggest the importance of stable circadian environments for fetuses to achieve sound physiology and intrauterine development. This idea is also supported by epidemiological and animal studies, in which pregnant females exposed to repeated shifting of light-dark cycles had increased rates of reproductive abnormalities and adverse pregnancy outcomes. In response to such findings, artificial circadian environments with light-dark (LD) cycles have been introduced to NICUs to promote better physical development of preterm infants. Such LD cycles, however, may not be fully effective for preterm infants who are less than 30 weeks gestational age (WGA) since they are too premature to be adequately responsive to light. Instead, circadian rhythmicity of incubated preterm infants less than 30 WGA may be able to be developed through stimulation of the non-visual senses such as touch and sound.